UPAYA GURU DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI POWERPOINT PADA PEMBELAJARAN SOSIOLOGI - Utin Mutiara Fadillah; Izhar Salim; Imran Imran (Universitas Tanjungpura, 2020)
AbstractThe title of this research is The Role of Teacher in Developing Students critical thinking through Microsoft PowerPoint in Learning Sociology(A descriptive research at Year-11 Students of SMA Muhammadiyah 1 Pontianak). The general problem in this research is how the role of teacher in developingthe critical thinking of the students in analysing, recognizing, and solving problems in learning sociology by using powerpoint as the multimedia. The researcher used qualitative approach in this study. There were seven participants in this research, a sociology teacher and six students at year-11 of SMA Muhammadiyah 1 Pontianak. The research finding of this study indicates that teacher can develop students' critical thinking skills by showing them some examples such as pictures through powerpoint as the multimedia in teaching Sociology and making the examples related to the students daily life. The developing of students critical thinking skills is also evidenced by looking at the students skills in analysing, recognizing, and solving problem in learning sociology in classroom. The students were able to understanding the material that given by the teacher properly and they were good in concluding and giving feedbacks about the material. Keyword: Microsoft Powerpoint, Students Critical Thinking, Teachers Role